Iodinated contrast media inhibit oxygen consumption in freshly isolated proximal tubular cells from elderly humans and diabetic rats: Influence of nitric oxide. (2nd January 2016) - Liss, Per; Hansell, Peter; Fasching, Angelica; Palm, Fredrik
Abstract: Objectives Mechanisms underlying contrast medium (CM)-induced nephropathy remain elusive, but recent attention has been directed to oxygen availability. The purpose of this study was to evaluate the effect of the low-osmolar CM iopromide and the iso-osmolar CM iodixanol on oxygen consumption (QO2 ) in freshly isolated proximal tubular cells (PTC) from kidneys ablated from elderly humans undergoing nephrectomy for renal carcinomas and from normoglycemic or streptozotocin-diabetic rats. Materials PTC were isolated from human kidneys, or kidneys of normoglycemic or streptozotocin-diabetic rats. QO2 was measured with Clark-type microelectrodes in a gas-tight chamber with and without each CM (10 mg I/mL medium). L-NAME was used to inhibit nitric oxide (NO) production caused by nitric oxide synthase. Results Both CM reduced QO2 in human PTC (about –35%) which was prevented by L-NAME. PTC from normoglycemic rats were unaffected by iopromide, whereas iodixanol decreased QO2 (–34%). Both CM decreased QO2 in PTC from diabetic rats (–38% and –36%, respectively). L-NAME only prevented the effect of iopromide in the diabetic rat PTC. Conclusions These observations demonstrate that CM can induce NO release from isolated PTC in vitro, which affects QO2 . Our results suggest that the induction of NO release and subsequent effect on the cellular oxygen metabolism are dependent on several factors, including CM type and pre-existing risk factors for the development of CM-induced nephropathy.